2014
DOI: 10.1007/s10120-014-0441-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of reduced-port laparoscopic total gastrectomy in gastric cancer preserving the pancreas and spleen

Abstract: Background The feasibility of using reduced-port laparoscopic total gastrectomy (RPLTG) for the treatment of gastric cancer remains unclear. This study aimed to address the potentially important advantages of this surgical technique. Methods Between April 2002 and February 2014, 90 patients underwent laparoscopy-assisted total gastrectomies, performed by a single surgeon. Of these, 45 patients underwent RPLTG and 45 patients underwent conventional laparoscopy-assisted total gastrectomy (CLATG). Shortterm outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…Predictive parameter may be the number of retrieved lymph nodes. In addition, that of previous reports was 36.5 (range, , which seemed to be comparable with that of CLG (7,11,14,17,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The long-term results can be expected.…”
Section: Oncological Validitysupporting
confidence: 85%
See 2 more Smart Citations
“…Predictive parameter may be the number of retrieved lymph nodes. In addition, that of previous reports was 36.5 (range, , which seemed to be comparable with that of CLG (7,11,14,17,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The long-term results can be expected.…”
Section: Oncological Validitysupporting
confidence: 85%
“…The term RPLG can be applied to various procedures with various efforts to achieve minimal invasiveness. Many literatures indicated that RPLG procedures are comparable with CLG procedures (11,(35)(36)(37)(38)(39)(40)(41). The present authors' concept of RPLG was derived from SILG.…”
Section: Reduced-port Laparoscopic Gastrectomymentioning
confidence: 87%
See 1 more Smart Citation
“…Although current surgical procedures for LTG have not yet been widely established and standardized, reports have appeared concerning the application of more advanced techniques, such as robotic total gastrectomy [64,65] and reduced-port LTG [66,67]. Robotic gastrectomy has been reported to provide manipulations as reliable as those provided by LTG.…”
Section: Discussionmentioning
confidence: 99%
“…Kunisaki et al 43 and Kawamura et al 44 compared conventional LTG with dual-port LTG (Table 5). Kunisaki et al reported that the operative time was significantly longer with dual-port LTG (319.0 min) than with conventional LTG (259.0 min).…”
Section: Dual-port or Single-port Ltgmentioning
confidence: 99%